A potent series targeting the malarial cGMP-dependent protein kinase clears infection and blocks transmission - David A. Baker; Lindsay B. Stewart; Jonathan M. Large; Paul W. Bowyer; Keith H. Ansell; María B. Jiménez-Díaz; Majida El Bakkouri; Kristian Birchall; Koen J. Dechering; Nathalie S. Bouloc; Peter J. Coombs; David Whalley; et al. (Nature Communications, 2017)
Protein kinases are promising drug targets for treatment of malaria. Here, starting with a medicinal chemistry approach, Baker et al. generate an imidazopyridine that selectively targets Plasmodium falciparum PKG, inhibits blood stage parasite growth in vitro and in mice and blocks transmission to mosquitoes.